Catlicious / Nurkhalida Suraya Jamaludin and Sharon Livan Ujang - Jamaludin, Nurkhalida Suraya; Ujang, Sharon Livan (2022)
This project requested us to write a report on online businesses that use the Facebook page platform. To advertise their goods, the student must construct a brand and create a Facebook profile. To market our brand, we must use all e-commerce methods such as teaser, soft sales, and a hard sell on the company page. To legitimate our internet business, we must also register for an E-commerce platform with MDEC. For this assignment, we name our business Catlicious, we sell repack cat food from the Greens brand. We provide 1kg of the repack packaging because for those who are the first time want to try our product. The flavour that we have is chicken and seafood. Greens are super-premium grade which is the food does not have food colouring that can affect a cat's health. By giving the best price with good quality food, the cat parent will be happy with the result. For the targeting market, the main areas that have been highlighted within Shah Alam, Selangor since Khalida was staying there. Not only within that areas, but the targeting market also would be within Malaysia as we can do a postage service. The business starts operating in June 2022 officially on our Facebook Page with the name of Catlicious. We were sure that our product will be well known by the people as we ensure that we will give the best product to fulfil our customer demand.